Monitoring and assessment activities and indications of empathic behavior of the examined teachers during physical education lessons - Muszkieta, Radoslaw; Oleśniewicz, Piotr; Cieślicka, Mirosława; Napierała, Marek (Journal of Education, Health and Sport, 2015)
Muszkieta Radosław, Oleśniewicz Piotr, Cieślicka Mirosława, Napierała Marek. Monitoring and assessment activities and indications of empathic behavior of the examined teachers during physical education lessons. Journal of Education, Health and Sport. 2015;5(12):678-685. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44813 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A678-685 https://pbn.nauka.gov.pl/works/695883 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Muszkieta Radosław, Oleśniewicz Piotr, Cieślicka Mirosława, Napierała Marek. Monitoring and assessment activities and indications of empathic behavior of the examined teachers during physical education lessons. Pedagogy and Psychology of Sport. 2015;1(1):4-10. eISSN pending. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.12.2015. Revised 25.12.2015. Accepted: 29.12.2015. Monitoring and assessment activities and indications of empathic behavior of the examined teachers during physical education lessons Radosław Muszkieta *, Piotr Oleśniewicz **, Mirosława Cieślicka ***, Marek Napierała *** * Academy of Sports and Science, Poland ** University School of Physical Education, Wrocław, Poland *** Kazimierz Wielki University, Bydgoszcz, Poland Keywords: physical education lessons, teachers, empathic behavior, evaluation Abstract The material of the studies was the physical education teachers of randomly chosen Poznań (Poland) schools: primary, grammar, and secondary schools. The studies involved 584 physical education teachers. The studies were conducted in the school year of 1999-2000. For the studies, an observation method was applied consisting in lesson observations during physical education lessons carried out by physical education teachers. The results of the studies form characteristic upward or downward tendencies. The higher the educational stage the higher the percentage value for the teachers who: a) assess attitudes and behavior of the students; b) monitor and assess knowledge of the students in the field of physical culture; c) assess with grades or points motor and organizational skills; d) assess verbally tasks’ achievement; e) apply and introduce self-monitoring and self-assessment of knowledge, skills, attitudes, and physical fitness of the students. The downward tendencies were observed exclusively for monitoring attitudes and behavior of the students (i.e. having sports outfit, activity, involvement, attendance, etc.). The examined women were characterized by better and more positive empathic behavior. For all parameters, the women appeared to be better.